Manusia dalam Filsafat Eksistensi Karl Theodor Jaspers - Juhansar, Juhansar (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2022)
Humans, as rational animals, are unique creatures with obligations and responsibilities. As rational animals, humans can process and solve their problems and strengthen the nature and purpose of their lives. This study aims to describe Karl Theodor Jaspers' views about humans from the perspective of philosophy, i.e., the enlightenment of existence and boundary situations. This article is descriptive qualitative philosophical research relays on a literature study. Literature data, primary and secondary, were analyzed using the philosophical hermeneutic method concerning verstehen and interpretation. This study shows that existentialism does not preoccupy the